Developmental Idealism: The Cultural Foundations of World Development Programs - Thornton, Arland (Sociol Dev (Oakl), 2015)
This paper extends theory and research concerning cultural models of development beyond family and demographic matters to a broad range of additional factors, including government, education, human rights, daily social conventions, and religion. Developmental idealism is a cultural model—a set of beliefs and values—that identifies the appropriate goals of development and the ends for achieving these goals. It includes beliefs about positive cause and effect relationships among such factors as economic growth, educational achievement, health, and political governance, as well as strong values regarding many attributes, including economic growth, education, small families, gender equality, and democratic governance. This cultural model has spread from its origins among the elites of northwest Europe to elites and ordinary people throughout the world. Developmental idealism has become so entrenched in local, national, and global social institutions that it has now achieved a taken-for-granted status among many national elites, academics, development practitioners, and ordinary people around the world. We argue that developmental idealism culture has been a fundamental force behind many cultural clashes within and between societies, and continues to be an important cause of much global social change. We suggest that developmental idealism should be included as a causal factor in theories of human behavior and social change.